Aptidão física relacionada à saúde e desempenho acadêmico de adolescentes - Castro, Fábio Jorge Santos de (2016)
Introduction: adequate levels of physical fitness are known for health benefits, it is possible to relate them to prevention of various diseases. However, the association between physical fitness and academic performance has not been established in the literature and has been a current concern, considering the development process of the human being in a global context. Objective: verifying the association between physical fitness related to health components and academic performance of adolescents. Methods: a descriptive cross-sectional study. The sample consisted of 326 adolescents aged between 15 and 18 years in a federal public educacional institution in the state of Sergipe. Data relating to physical fitness (body composition (BC), flexibility (FLEX), muscular strength/endurance (MSE) and cardiorespiratory endurance (CE)) were collected by applying the tests of American Alliance for Health, Physical Education, Recreation and Dance battery and those related to academic performance (grades of the disciplines that comprise the three areas of knowledge: languages and code (LC), natural sciences (NS) and human sciences (HS)) were obtained from the school report coordination of the institution. It was used the binary logistic regression analysis for association between variables. Results: the girls presented less prevalence of unfitness (p<0.05) in FLEX and the boys in MSE. In BC and CE, there was no difference between the groups (p 0.05). On academic performance, the prevalence of overall approval rating was 86.3%, with no significant difference (p 0,05) between the performances of the groups in the three areas of knowledge together and alone in the area of HS. However, in the areas of LC and NS, the girls presented superior performance than the boys do (p<0.05). The area of NS presented the highest prevalence (p<0.05) of unfit, 24.5%, against 12.8% of HS and 8.8% of LC. There was no association of BC, Flex and MSE with academic performance (p 0,05), however, CE was associated (p=0.038; OR=2.39; CI95%=1.05-5.44). Conclusion: there was association between cardiorespiratory disabilty and bad academic performance of adolescents.